2018
DOI: 10.4103/ijmr.ijmr_644_16
|View full text |Cite
|
Sign up to set email alerts
|

AdeR-AdeS mutations & overexpression of the AdeABC efflux system in ciprofloxacin-resistant Acinetobacter baumannii clinical isolates

Abstract: Background & objectives:Overexpression of efflux pumps is a cause of acquired resistance to fluoroquinolones in Acinetobacter baumannii. The present study was done to investigate the presence and overexpression of AdeABC efflux system and to analyze the sequences of AdeR-AdeS regulatory system in ciprofloxacin-resistant A. baumannii isolates.Methods:Susceptibility of 50 clinical A. baumannii isolates to ciprofloxacin, imipenem, ceftazidime, cefepime and gentamicin antimicrobials was evaluated by agar dilution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 30 publications
3
25
1
Order By: Relevance
“…The impact of multiple resistance mechanisms in the success of A. baumannii as a notorious pathogen has led to confined treatment regimens for this tenacious microorganism [ 1 ]. In the present study, the majority of isolates showed an increased rate of resistance to all the first-line antibiotics in comparison to a previous study from Tehran, Iran [ 32 ]. Although carbapenems are the mainstay of treatment, all of our XDR isolates were resistant to carbapenems.…”
Section: Discussioncontrasting
confidence: 70%
“…The impact of multiple resistance mechanisms in the success of A. baumannii as a notorious pathogen has led to confined treatment regimens for this tenacious microorganism [ 1 ]. In the present study, the majority of isolates showed an increased rate of resistance to all the first-line antibiotics in comparison to a previous study from Tehran, Iran [ 32 ]. Although carbapenems are the mainstay of treatment, all of our XDR isolates were resistant to carbapenems.…”
Section: Discussioncontrasting
confidence: 70%
“…Table 4 lists all recorded quinolone-specific resistance mechanisms for A. baumannii. Quinolone resistance occurring secondary to overactive RND pumps has been long documented and is quite common [128]. Mutations in the TCS elements regarding both regulator (AdeR, primarily with polymorphisms D20N, A91V, A136V, and P116L) and sensor (AdeS, mainly due to polymorphisms G30D, A94V, G103D, G186V, and T153M) of AdeABC pump result in higher fluoroquinolone efflux.…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…In our study, we found that both ABC transporter, MFS transporter, and RND transporter were up-regulated. MFS efflux pump and ABC transporter have been found to be associated with quinolone resistance and beta lactam resistance ( Correia et al., 2016 ; Xiao et al., 2016 ; Lari et al., 2018 ; Pérez-Varela et al., 2018 ). T1SS is formed by HlyB (ABC transporter), HlyD (membrane fusion protein), and TolC (outer membrane).…”
Section: Resultsmentioning
confidence: 99%